Quality of Life and Cost Considerations: Y-90 Radioembolization - Williams, Stephen J.; Rilling, William S.; White, Sarah B. (Seminars in Interventional Radiology, 2021)
Objective Transarterial radioembolization (TARE) offers a minimally invasive and safe treatment option for primary and metastatic hepatic malignancies. The benefits of TARE are manifold including prolonged overall survival, low associated morbidities, and improved time to progression allowing prolonged treatment-free intervals. The rapid development of new systemic therapies including immunotherapy has radically changed the treatment landscape for primary and metastatic liver cancer. Given the current climate, it is critical for interventional oncologists to understand the benefits of TARE relative to these other therapies. Therefore, this report aims to review quality-of-life outcomes and the cost comparisons of TARE as compared with systemic therapies.
Keywords: transarterial radioembolization; health-related quality of life; yttrium 90; hepatocellular carcinoma; transarterial chemoembolization; interventional radiology